Pride, prejudice, and other flavors : a novel - Dev, Sonali (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"Award-winning author Sonali Dev launches a new series about the Rajes, an immigrant Indian family descended from royalty, who have built their lives in San Francisco."--